Development of eco-friendly PVA/iron oxide nano-membranes synthesized via green methods for efficient removal of microbial and chemical contaminants from drinking water - Rizwana Parveen; Farhat Yasmeen; Muhammad Iqbal (Applied Water Science)
Abstract Ensuring access to clean and safe drinking water is a critical component of a healthy lifestyle. In this study, we report the development of a novel eco-friendly polyvinyl alcohol (PVA)/iron oxide nano-membrane synthesized using a green method for iron oxide nanoparticle production. This work is distinctive in its integration of green-synthesized iron oxide nanoparticles into a flexible, reusable PVA matrix, forming a next-generation membrane with multifunctional water purification capabilities. The nanoparticles, with an average size of 10 ± 9 d.nm, were characterized using SEM, nano zeta sizer, FTIR, and UV–Vis spectroscopy, confirming their nanoscale morphology and functional properties. The fabricated nano-membrane was evaluated for its efficacy in treating drinking water samples from diverse geographic regions of Wah Cantt, Attock, and Taxila, Pakistan, making this one of the few studies to test real-world water samples using green nano-membranes. Results indicated that nano-membrane acts as a highly effective disinfectant against microbes, turbidity decreased by 88.8%, from 40 NTU to 4.48 NTU, sodium content reduced by 28%, from 43 mg/L to 31 mg/L, total hardness decreased by 9.4%, from 519 mg/L to 470 mg/L, nitrate levels dropped by 63.5%, from 49.9 ppm to 18.2 ppm, and pH decreased slightly by 2.6%, from 7.28 to 7.09. This study introduces a sustainable, cost-effective, and scalable approach to membrane-based water purification, providing a valuable framework for the design of future nano-enabled filtration systems. The novelty lies not only in the green synthesis and practical application of the nano-membrane, but also in its demonstrated real-world performance across varied water sources, making it a promising candidate for widespread deployment in resource-limited settings.